ENHANCING CRITICAL THINKING SKILLS OF FUTURE LANGUAGE SCHOLARS IN PEDAGOGICAL COURSES - Liliya Baranovska; Liliya Morska; Iryna Simkova; Alla Zasluzhena (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
The paper reports on the results of critical thinking enhancement during the training of future language scholars in a Comparative Pedagogy course. 61 future language scholars from Poland and Ukraine took part in the research. The mixed research was based on the qualitative and quantitative analysis of students' responses regarding critical thinking enhancement after completing the course. Informal interviews and diagnostic tests were used. For the verification of results, we applied Fisher's Exact Variance Test (F-test). The results show that most respondents (91%) enhanced their skills and abilities in critical thinking: differentiating information (76%), categorising information (62%), comparing information (85%), estimating information (87%), analysing and synthesising information (91%). The findings of this study support the idea that students' critical thinking skills can be successfully developed in pedagogical courses.